2019
DOI: 10.1108/jm2-05-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Presenting sustainable supply chain fuzzy rotation matrix framework to manage business challenges in the context of sustainable supply chain management

Abstract: Purpose The purpose of this paper seeks to provide a hybrid framework of sustainable supply chain fuzzy rotation matrix regarding the challenges in today’s business environment and the goals pursued by sustainable supply chain, to prioritize effective infrastructure to manage the challenges in ceramic tile industry in Yazd. Design/methodology/approach The research offers a hybrid framework of analytical hierarchy process (AHP) and quality function deployment (QFD) model to determine, which one of the goals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…For example, a study on evaluating barriers to designing green supply chain practices in the West African cashew industry suggested enhancing how environmental performance is measured, distributors collaborating with national and regional governments to formulate and implement practices in GSCM, factory staff members increasing their capacity to examine and report environmental data, and increasing demand as key strategies (Agyemang et al., 2018). Another study in the ceramic industry reported attention of recycling, applying green engineering principles in the production process, and changes of organizational goals to environmental goals as essential strategies (Jalilian & Migghafoori, 2020). Scholarship has also emphasized multi‐stakeholder initiatives as a promising pathway to address GSCM challenges (Fowler & Biekart, 2017) and the formulation of regulatory processes and standards to conduct ethical trades (Huges, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a study on evaluating barriers to designing green supply chain practices in the West African cashew industry suggested enhancing how environmental performance is measured, distributors collaborating with national and regional governments to formulate and implement practices in GSCM, factory staff members increasing their capacity to examine and report environmental data, and increasing demand as key strategies (Agyemang et al., 2018). Another study in the ceramic industry reported attention of recycling, applying green engineering principles in the production process, and changes of organizational goals to environmental goals as essential strategies (Jalilian & Migghafoori, 2020). Scholarship has also emphasized multi‐stakeholder initiatives as a promising pathway to address GSCM challenges (Fowler & Biekart, 2017) and the formulation of regulatory processes and standards to conduct ethical trades (Huges, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the past few years, environmental regulations and production standards have become stern and are so-called “green challenges” for international trade (Jalilian and Mirghafoori, 2020). These challenges affect the trading revenue of developing countries, as they require a complete reformation of the technical input and also the application of green practices in the production model (Su et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For Jalilian and Mirghafoori (2020), a sustainable supply chain need to consider environmental and social negative impacts throughout the chain and, for social impacts assessment, different kinds of stakeholders need to be considered, from customers to government. Shokouhyar et al (2019) highlights that in a sustainable supply chain positive economic results are still a core target, however, social and environmental impacts also need to be considered.…”
Section: Sustainability In Supply Chain Managementmentioning
confidence: 99%
“…The insertion of sustainability concepts in the supply chain management field is widely debated in the literature (Jalilian and Mirghafoori, 2020; Vanalle et al , 2017). Dubey et al (2017) state that the literature fails in properly understanding the concept of sustainable supply chain both from a theoretical and managerial point of view, with overlaps among the green supply chain management literature, environmental supply chain management and sustainable supply chain literature, as well as other areas that have attracted products such as environmental supply chains, ethical supply chains and responsible supply chains.…”
Section: Theoretical Basementioning
confidence: 99%